Induced forming modes in a pre-consolidated woven polypropylene composite during stretch forming process at room temperature: I. Experimental studies. (January 2015) - Zanjani, N.A.; Sexton, A.; Kalyanasundaram, S.
Abstract: In the current study, rectangular specimens of pre-consolidated woven Self-Reinforced Polypropylene (SRPP) possessing different fibre orientations and aspect ratios were stretch formed in an open die. Induced displacements were recorded by an in-situ 3D photogrammetric measurement system. Resultant principal strains were investigated to clarify the role of different deformation modes during stamp forming. The dependency of induced deformation modes to the specimens' geometries was studied. A novel path/deformation dependent failure criterion was established to distinguish between safe and failed regions of SRPP in a stamping process and to elucidate the dependency between failure and induced forming modes in a woven composite. The experimental results highlighted the suitability of consolidated SRPP to be formed into complex doubly curved geometries by the stamp forming process at room temperature. It was found that required forming depths could be achieved if a proper combination of specimen size, boundary condition, and fibre orientation was selected.